2013
DOI: 10.1179/1476830513y.0000000096
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of complex milk lipid concentrate (CMLc) improved the memory of aged rats

Abstract: The data suggested that the supplementation of CMLc during the early stage of brain aging may prevent memory decline possibly through improving vascular and neuronal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…Gelatin cubes were used for administration of the dietary supplements, which were formulated using raspberry flavouring and gelatin (10% w/v) containing sucrose (10% w/v) as previously described [32, 33, 36, 44]. Briefly, the MFGM mixtures were dissolved in water using a food processor and were then mixed with 1 L of gelatin/sucrose mixture at 50 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelatin cubes were used for administration of the dietary supplements, which were formulated using raspberry flavouring and gelatin (10% w/v) containing sucrose (10% w/v) as previously described [32, 33, 36, 44]. Briefly, the MFGM mixtures were dissolved in water using a food processor and were then mixed with 1 L of gelatin/sucrose mixture at 50 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, MFGM composites including PLs [24], sphingolipids [26, 27] and gangliosides [2830] have purported positive effects on neuroplasticity. For example, dietary supplementation with bovine-derived MFGM mixtures has recently been reported to promote post-natal neurodevelopment [3135] and to limit age-associated neural decline in elderly animals [36]. …”
Section: Introductionmentioning
confidence: 99%
“…Complex milk lipids (CML), as a source of GA, have potential benefits for brain development. [19][20][21] The rate of GA accretion in the developing brain is highest in utero and in early neonatal life. 22 23 Preclinical research has shown that CML are transferred across the placenta and as such, an increased maternal intake of CML in pregnancy has been associated with increases in fetal GA levels.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in synaptic plasticity in these brain regions, for example, dopamine outputs and glutamate receptors, may be the biological modifications underlying the observed improvements in learning and memory ( 8 , 9 , 11 ). Synaptophysin is a marker for synaptic vesicles and has been commonly used as a marker for synaptic plasticity at pre-synaptic location ( 12 , 13 ). Improved dopamine neurotransmission has been reported to be associated with improved memory in aged rats after long-term supplementation with a concentrate of dairy lipids ( 12 ).…”
mentioning
confidence: 99%
“…Synaptophysin is a marker for synaptic vesicles and has been commonly used as a marker for synaptic plasticity at pre-synaptic location ( 12 , 13 ). Improved dopamine neurotransmission has been reported to be associated with improved memory in aged rats after long-term supplementation with a concentrate of dairy lipids ( 12 ). In addition to a supporting role for astrocytes in neuronal and synaptic plasticity ( 14 ), neuronal–glial–vascular networking plays an essential role in neuronal function ( 15 ) and myelination ( 16 ).…”
mentioning
confidence: 99%